Grundtvig og Kingos salmer - Stevns, Magnus (Grundtvig-studier, 1949)
Grundtvig and Kingo's Hymns. By Magnus Stevns When Grundtvig began writing hymns he definitely took Thomas Kingo, the greatest Danish hymn-writer of the 17th century, as his model. From childhood Grundtvig had loved “ Kingos Salmebog” (“ Kingo’s Hymn-book” , 1699) and the living interpretation of Bible history which its hymns contained. He was therefore in dire distress when as a clergyman he was obliged to use the new so-called “ Evangelisk christelig Psalmebog” (“ Evangelical Christian Hymnbook”, 1798), a book of extremely poor quality from both the Christian and the poetic point of view. Kingo’s hymns on the Passion, describing the sufferings and death of Jesus with intense feeling, and his genuinely Lutheran hymns about the battle against the Devil, the world and our flesh which the child of God has to fight, were replaced by insipid moral verses about the Christian virtues. Lifeless abstract terminology was universally substituted for the concrete, personal phraseology of the Bible, e. g., “evil” instead of “ the Evil one” or “ the Devil” , “ the Lord God” instead of the personal “ thy Saviour”. Grundtvig wished to renew Danish hymn-writing with the support of what was best in the past; but in spite of his love for Kingo’s hymns, with their historical stamp and evangelical imagery, he found it necessary, partly to shorten most of them, and partly to alter those things in them which did not agree with his own conception of Christianity. In Grundtvig’s adaptations of Kingo’s hymns one notices how he tones down or omits Kingo’s forceful descriptions of the humiliation and mocking of Jesus; while Kingo dwells chiefly on the sufferings of Good Friday, and pictures the agony of Jesus as He drank the cup of God’s anger to the dregs, for Grundtvig the central point is the victory over death which Jesus won for us, and His rising again to life for us. In Grundtvig’s opinion, Kingo’s hymns overstress the distance between God and man; Grundtvig stresses the view that in baptism the Christian comes into fellowship with God and thereby has received grace and has shared in the Atonement. Nor can Grundtvig share Kingo’s conception of the death of the body as a release which helps the soul out of the body’s wretched “worm-bag”. In Grundtvig’s view death is the last enemy which we shall overcome with God’s help, and therefore the Christian hope attaches itself first and foremost to the risen Saviour. In his revision of Kingo Grundtvig usually preserves his intonation and many words and images, but in other respects permits himself such extensive alterations that the poet Ingemann, with good reason, was obliged to say of i t : “ However closely akin to Kingo’s your spirit may be, I find that your strongly-marked characteristics will not blend together with his sufficiently to prevent me from hearing now the voice of one, now that of the other” . All the same Grundtvig often shows himself as the remodeller with a touch of genius, who not only remodels the hymn, but makes a new creation of it (this is the case with Grundtvig’s “ I Nasareth, i trange Kaar”, “ In Nasareth, in needy state” ). In many cases Grundtvig’s relation to Kingo’s hymns is one of reaction rather than of imitation, as may be seen from a comparison between Kingo’s “ Kommer, I som vil ledsage” (“ Come, ye who will accompany. . . ” ) and Grundtvig’s “ Tag det sorte Kors fra Graven!” (“ Take the black cross from the grave!” . . . ). Here Grundtvig “sings against” Kingo almost line by line. In one of his best known poems, “ Jeg kender et Land” (“ I know a land” — later rewritten as the hymn “ O Kristelighed”, “ O Christian faith!”), Grundtvig uses the metre which Kingo employed in his great hymn “ Far Verden Farvel” (“ Farewell to the world” ), but for Kingo’s renunciation of the life of the world Grundtvig substitutes his positive confession of faith in God’s kingdom of love. The relation between the two hymn-writers may be summed up thus: both constantly seek for union with the Deity through an imitation which — though feebly — makes the way of man resemble that of the Deity. But for Kingo the Deity Himself, Who is God and man, is most human (and therefore capable of being imitated) before Golgotha, and most divine (far removed from man) after the Resurrection, while the opposite is the case with Grundtvig, for whom the Risen One is “ flesh in heaven, spirit on earth”. For Grundtvig it would be unreasonable to believe that man’s powers were equal to imitating the Deity, “ Christ, Who died upon the cross”, before he could imitate the man, “ Jesus, Who rose from the grave”. Kingo reaches the following conclusion: “ Only when by death I truly bid the world farewell, then only shall I be at home with God,” while Grundtvig arrives at another, namely: “ Only when God is at home in me, then only can I truly bid the world farewell.” When Kingo has first learnt to know the power of Jesus’ Passion, he will afterwards learn to know the community and fellowship of His Resurrection. But Grundtvig says, “ The Lord wishes all who believe in Him to learn to know the power of His Resurrection before they feel themselves called to the community and fellowship of His sufferings.” (Cp. Philipp, ch. 3, v. 10.) Therefore it is the first task of Grundtvig’s hymns to renew the song of praise to the risen Saviour, who through the Holy Spirit is present in the Church; in Grundtvig’s hymns it is Whitsun before it is Easter. But Grundtvig (as he himself stresses) has not “ concealed the fact that Our Lord Jesus Christ in His Passion and death must stand for us both as our Saviour and as our example”. In Grundtvig’s poetic activity this gives rise to “a song of the secret chamber”, which sounds more subdued, but in purity & depth of tone excels both the festal hymns of “ Sangværket” (“ The Hymn-Book” ) and Kingo’s “ trumpet songs” .